Translation and validation of the Indonesian version of the diabetic foot ulcer scale–short form (DFS-SF): a psychometric evaluation - Haryanto, Haryanto; Abdul Wahab, Patimah; Ong, Mei Fong; Lestari, Lilis; Hastuti, Lidia; Pratama, Kharisma (Asia Pacific Higher Learning Sdn. Bhd., 2026)
Background: Diabetic Foot Ulcer (DFU) is a common chronic complication of diabetes that significantly impairs patients' quality of life. However, a culturally adapted and validated Indonesian DFU specific quality of life instrument to support comprehensive nursing assessment is not yet available. Objective: This study aimed to adapt the DFS-SF (Diabetic Foot Ulcer Scale) into Indonesian using a standardized translation process and to evaluate its psychometric properties, specifically validity and reliability. Methods: This study used a cross-sectional quantitative design and recruited 118 patients from three urban wound care clinics. The original DFS-SF underwent forward-backward translation and cultural adaptation. Internal consistency and construct validity were examined using PLS-SEM (Partial Least Squares Structural Equation Modeling) analysis. Results: The Indonesian DFS-SF demonstrated robust psychometric properties, including high reliability and validity across all domains. Strong internal consistency was observed across all domains, with both Cronbach's alpha and composite reliability > 0.80. The construct demonstrated adequate convergent validity, evidenced by Average Variance Extracted (AVE) values of 0.60 or higher, and by employing the Fornell-Larcker criterion, discriminant validity was verified. Outer loadings for most indicators were above 0.70, with particularly high loadings for Leisure (≥0.95) and daily activity (≥0.91) domains, indicating robust construct measurement. Conclusion: The Indonesian version demonstrated validity and reliability for assessing quality of life in patients with DFU. To enhance generalizability, future studies should include more diverse populations. This research suggests that the Indonesian version of the DFS-SF can be effectively applied in clinical settings to assess the quality of life among patients with diabetic foot ulcers.